The American record : images of the nation's past - Graebner, William; Richards, Leonard (New York : Alfred A. Knopf, 1982)
In this book, we have attempted to bridge the gap between the old history and the new, to graft the excitement of modern approaches to history on an existing framework with which most of use feel comfortable.
Chapter 1. Reconstruction -- Chapter 2. The gilded age: industrial transformation and the dream of order -- Chapter 3. The city -- Chapter 4. New frontiers and new problems -- Chapter 5. Empire, crisis and reform -- Chapter 6. Progressivism: the age of reform -- Chapter 7. The 1920s: from was to normally -- Chapter 8. Herbert hoover and the age of consumer -- Chapter 9. The great depression and the new deal -- Chapter 10. From a new deal to a new world war.
Keywords: UNITED STATES -- HISTORY